THE EFFECT OF COST STRUCTURE, OPERATIONAL EFFICIENCY AND PRICING ON PROFITABILITY OF PRODUCTS AND SERVICES AT PT. UNILEVER PERIOD 2016-2023 - Gunawan, Edi; Sofiana, Maya; Pasaribu, Betsy Tiurma; Hanjaya, Yahya Kurnia; Agustiani, Anita (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the effect of cost structure, operational efficiency and pricing on product and service profitability. This study was conducted at PT. Unilever listed on the Indonesia Stock Exchange for the 2016-2023 period. This study is a quantitative research type. The research method used is secondary data analysis, with the main source being the annual financial report of PT Unilever Indonesia Tbk. The population in this study was all annual financial reports of PT Unilever Indonesia Tbk, the sample taken using purposive sampling technique, namely selecting data for eight years (2016–2023). The analysis used in this study is the analysis instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing using IBM SPSS Statistics Version 26. The results of the study indicate that the cost structure shows that it partially has a positive and significant effect on product and service profitability. Operational Efficiency shows that it partially has no effect on product and service profitability. Pricing shows that it partially has a positive and significant effect on product and service profitability. Cost structure, operational cost efficiency, pricing show that they simultaneously have a positive and significant effect on product and service profitability. Further research is suggested to explore the role of moderating variables such as product innovation and service quality in strengthening the relationship between cost structure, operational efficiency, and pricing on profitability, as well as expanding the research object to other industrial sectors.